Effectiveness of Early Detection of Leptospirosis in Tropical Developing Countries: A Literature Review - Agustin Hanapi, Abe Yafi Muqaddas (UNIVERSITAS BENGKULU, 2025)
Early detection of leptospirosis is critical for effective disease management and reducing mortality, particularly in tropical developing countries where the disease burden is high and clinical presentation resembles other febrile illnesses such as malaria and dengue. The incidence of leptospirosis can escalate dramatically following flooding disasters, with mortality rates substantially increasing. This review assesses the effectiveness of various early detection methods, including molecular techniques (PCR), serological assays, rapid lateral flow immunoassays (LFIs), and geospatial early warning systems. LFIs demonstrate moderate sensitivity ( 68%) and high specificity ( 93%), indicating potential utility for screening in endemic areas, although they require confirmatory testing to ensure diagnostic accuracy. IgM-based assays show superior sensitivity compared to IgG-based methods, suggesting greater promise for early diagnosis. Despite advancements, challenges remain in optimizing diagnostic tools suitable for resource-limited tropical settings to enable timely and accurate detection. This underscores the need for integrated early warning systems combined with improved diagnostic technologies to enhance leptospirosis control and prevention strategies.